2017
DOI: 10.21475/poj.10.02.17.pne364
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics differentiation of oil palm (Elaeis guineensis Jacq.) spear leaf with contrasting susceptibility to Ganoderma boninense

Abstract: Basal stem rot (BSR) disease caused by Ganoderma boninense is the most serious and destructive disease in oil palm, especially in Southeast Asia and required urgent control measures to combat the disease outbreak. Information of understanding metabolite response of oil palm to BSR is limited. Therefore, parental palms with contrasting susceptibility to G. boninense based on previous oil palm progenies testing using root inoculation technique to identify oil palm progenies partially tolerant and susceptible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The representative 1 H-NMR spectra of OPL samples extracted by different polarities of solvents is displayed in Figure 1. Previous studies on OPL have reported primary and secondary metabolites, which are organic acids, amino acids, simple carbohydrates, phenolic acids, luteolin, and apigenin derivatives [8,9,[23][24][25][26]. Nevertheless, the data with regard to the secondary metabolites present in OPL are still considered limited.…”
Section: Visual Inspection Of 1 H-nmr Spectra Of Opl Extracts and Metmentioning
confidence: 99%
“…The representative 1 H-NMR spectra of OPL samples extracted by different polarities of solvents is displayed in Figure 1. Previous studies on OPL have reported primary and secondary metabolites, which are organic acids, amino acids, simple carbohydrates, phenolic acids, luteolin, and apigenin derivatives [8,9,[23][24][25][26]. Nevertheless, the data with regard to the secondary metabolites present in OPL are still considered limited.…”
Section: Visual Inspection Of 1 H-nmr Spectra Of Opl Extracts and Metmentioning
confidence: 99%
“…10 The presence of hexadecanoic acid is an important growth and defence mechanism against pathogen in EG. 11 Fatty acids have been shown to possess antimicrobial action; 12 while others have been implicated in pathway elucidation 13 and stimulation of resistance mechanism in plants. 14 Biologically active long chain fatty acids exert their effect on membrane phospholipids by modifying its composition and potentially replacing or interfering with the synthesis of phospholipid derived lipid signalling molecules, including endocannabinoids.…”
Section: Resultsmentioning
confidence: 99%
“…Oil palm is one of the most important sources of lignocellulosic biomass in Asia, especially in Malaysia and Indonesia. Malaysia, after Indonesia, is the world's second-largest producer of palm oil, with a capacity of 17.32 million tonnes and a cultivated area of 5.74 million ha [1]. According to the Malaysian Palm Oil Board (MPOB) statistics from 2016, the total volume of oil palm products was 25.64 million tonnes [2].…”
Section: Introductionmentioning
confidence: 99%